2020
DOI: 10.1002/1873-3468.14010
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome: friend and foe of mitochondrial biogenesis

Abstract: Most mitochondrial proteins are synthesized in the cytosol and subsequently translocated as unfolded polypeptides into mitochondria. Cytosolic chaperones maintain precursor proteins in an import‐competent state. This post‐translational import reaction is under surveillance of the cytosolic ubiquitin‐proteasome system, which carries out several distinguishable activities. On the one hand, the proteasome degrades nonproductive protein precursors from the cytosol and nucleus, import intermediates that are stuck i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 148 publications
2
28
0
Order By: Relevance
“…Thus, at normal Mia40 levels, a fraction of newly synthesized mitochondrial proteins is apparently never imported but retained in the cytosol and finally degraded. Recent studies indeed directly demonstrated the competition of the Mia40-mediated import and proteasomal degradation (Kowalski et al, 2018, Krämer, Groh et al, 2020, Mohanraj et al, 2019). Thus, increased Mia40 levels presumably speed up the import of certain proteins and thus might reduce their burden on cytosolic proteostasis.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, at normal Mia40 levels, a fraction of newly synthesized mitochondrial proteins is apparently never imported but retained in the cytosol and finally degraded. Recent studies indeed directly demonstrated the competition of the Mia40-mediated import and proteasomal degradation (Kowalski et al, 2018, Krämer, Groh et al, 2020, Mohanraj et al, 2019). Thus, increased Mia40 levels presumably speed up the import of certain proteins and thus might reduce their burden on cytosolic proteostasis.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, at normal Mia40 levels, a fraction of newly synthesized mitochondrial proteins is apparently never imported but retained in the cytosol and finally degraded. Recent studies indeed directly demonstrated the competition of the Mia40‐mediated import and proteasomal degradation (Kowalski et al , 2018; Mohanraj et al , 2019; Krämer, Groh et al , 2020). Thus, increased Mia40 levels presumably speed up the import of certain proteins and thus might reduce their burden on cytosolic proteostasis (Fig 8E, middle panel). The Mia40 pathway is only one out of several import routes into mitochondria.…”
Section: Discussionmentioning
confidence: 97%
“…Proteasomal degradation of ER and mitochondrial proteins (Figure 3) is often summarized under the umbrella terms ERAD (for ER-associated degradation) and MAD (for mitochondria-associated degradation) [86][87][88][89]. The components and underlying mechanisms of ERAD are rather well understood, and even structures of the ERAD machinery were recently published [90].…”
Section: Destructive Targeting Via Erad and Madmentioning
confidence: 99%